Karakteristik Kelayakan Teknologi RFID sebagai Kebutuhan Bisnis pada Perusahaan Logistik di Indonesia: Sistematik Literature Review - Erick Fernando; Derist Touriano; Dina Fitria Murad; Surjandy Surjandy (Jurnal SISKOM-KB (Sistem Komputer dan Kecerdasan Buatan), 2019)
Developments in information technology affects an organization to become more advanced and better. Logistics company is one of the companies to implement information technology. One of the technologies that can be implemented RFID technology. RFID is a chip that stores a record or data. Thus RFID technology can be used as business requirements on a company that can help all company activities. In this study will explore the feasibility of a characteristic of RFID technology can be applied or can as the business needs of the logistics company is INDONESIA. In this paper use you methods Systematic literature review (SLR). This research resulted in three RFID characteristics: Real-time data processing, data tracking continuous and discrete data, reuse. Expected by this research can contribute to how a user can select and measure the characteristics of RFID technology so that the views of the system and the implementation of RFID technology into added value for the company rather as complementary technologies.